The Acoustic City: Sonorous Landscapes, Urban Memory, and the Politics of Noise - Muhammad Hasan; Jovanka Andina; Matilda Munoz; Emir Abdullah; Ahmad Erza (Enigma Institute, 2025)
The contemporary city is often conceived through a visual paradigm, yet its character is profoundly shaped by its acoustic environment. This study investigated the urban soundscape as a complex tapestry woven from sound, memory, and power. Focusing on the rapidly urbanizing context of Indonesia, this research explored how sonorous landscapes are produced, experienced, and contested, shaping collective urban memory and becoming arenas for political negotiation. A mixed-methods approach was employed, integrating qualitative ethnographic research with quantitative acoustic analysis. Fieldwork was conducted in two distinct Indonesian urban settings: the megacity of Jakarta and the historically significant city of Palembang. Methods included 60 semi-structured interviews with residents, urban planners, and community leaders; 30 researcher-led soundwalks using participant observation; and acoustic data collection using Class 1 sound level meters at 100 strategic locations. This data was used to create predictive acoustic models of selected neighborhoods using CadnaA sound prediction software to visualize and analyze sound pressure level (SPL) distribution. The findings revealed a rich acoustic lexicon unique to Indonesian cities, characterized by a dynamic interplay of religious sounds (the call to prayer or adzan), commercial vocalizations (street vendor calls), transportation noise, and sounds of community life (gotong royong). Ethnographic data demonstrated that these sounds are potent carriers of urban memory, evoking nostalgia and a sense of belonging, but are also sources of significant social friction. Acoustic models identified